Practical causal hysteretic damping. - Nakamura, Naohiro (Earthquake engineering & structural dynamics.)
A number of experiments indicate that the internal damping corresponding to the energy dissipation of many materials is essentially frequency independent. Accordingly, an analysis model that can express such characteristics (called a hysteretic damping model) in the time domain is needed. Although a great number of investigations into this subject have been carried out, there are a few practical methods. In this paper, a simple hysteretic damping model which satisfies the causality condition is presented using an extension of the complex stiffness transfer method that the author has proposed. Compared with the energy proportional damping model and the Biot model, the applicability and the efficiency of this model to time history response analyses were confirmed well by example problems.